Big Papa and the time machine - Bernstrom, Daniel (Harper, an imprint of HarperCollins Publishers, 2020)
Discover the true meaning of being brave in this tender and whimsical picture book from Daniel Bernstrom (One Day in the Eucalytus, Eucalyptus Tree) and Shane Evans (Chocolate Me!) that follows a grandfather and grandson who travel through time in a beloved 1952 Ford.